Quality of life of caregivers of children with cerebral palsy of South Western Amazonia - doi: 10.5020/18061230.2012.p30 - Moretti, Gustavo de Souza (2012)
Objective: To assess the quality of life of caregivers of children with cerebral palsy attended in the Association of Parents and Friends of Exceptional Children (APAE), in Rio Branco-AC, in South Western Amazon, Brazil. Methods: This qualitative and exploratory study was held at an APAE facility in Rio Branco-AC with twelve caregivers. The study included caregivers of children with clinical diagnosis of cerebral palsy confirmed by medical report. Data collection was performed from September to October 2010 with a semi-structured interview, using a socioeconomic file and a questionnaire consisting of questions based on the World Health Organization Quality of Life-100 instrument, all interviews being audio-recorded and verbatim transcribed for further analysis and interpretation. Results: The results indicate that the psychological health and level of independence are the most compromised, considering that the caregivers dedicate their lives for taking care of the children since their birth, what leads them to be overloaded, not only physically but also psychologically, due to the impairment of the child. Conclusion: The quality of life of caregivers of children with cerebral palsy can be seen as unsatisfactory, especially regarding psychological aspects and level of independence.